In silico Pathogenomic Analysis of Corynebacterium Pseudotuberculosis Biovar Ovis - Blanco, Iago Rodrigues; Araújo, Carlos Leonardo; Folador, Adriana Carneiro (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2020: Anais do XIII Simpósio Brasileiro de Bioinformática, 2020)
Corynebacterium pseudotuberculosis is a pathogenic bacterium that may transmit caseous lymphadenitis, veterinary infection that severely attacks animals such as goats and sheep. It is known that the toxin Phosholipase D is the major virulence factor associated with this disease. However, genomic computational studies can reveal further information concerning pathogenicity mechanisms of bacteria. Through sequence analysis tools, it is possible to assess the genomic bases of these mechanisms and to analyze similarities among the different strains of this species. Nitrate reductase-negative bacteria are classified in the biovar ovis, able to transmit the infection. Thus, we developed an in silico comparative pathogenomic analysis with genomes of 33 strains of C. pseudotuberculosis biovar ovis strains, which cause caseous lymphadenitis. Looking for the identification of pathogenicity-related genes, virulence factors and composition of pathogenicity islands, it was possible to computationally predict pathogenicity potentials of target proteins and their respective biological processes during infection, besides identification of prophage genome elements and prediction of protein protein interactions.